Tourism Development And Coastal Ecosystem Degradation In Southern Bali - Donny Juliandri Prihadi; Tiago Costa; Gabriela Koleva (Yayasan Adra Karima Hubbi, 2025)
Background. Rapid tourism development in southern Bali has transformed the region into one of Indonesia’s most dynamic economic zones while simultaneously placing immense pressure on its coastal ecosystems. The expansion of hotels, restaurants, and recreational facilities has led to land-use change, increased waste discharge, shoreline modification, and coral reef degradation. The resulting imbalance between economic growth and ecological stability threatens the long-term sustainability of both the tourism industry and local livelihoods. Purpose. This study aims to examine the relationship between tourism development and coastal ecosystem degradation in southern Bali, focusing on spatial, ecological, and socio-economic dimensions. Method. A mixed-method approach was adopted, combining satellite imagery analysis, field observations, and stakeholder interviews. Spatial analysis using GIS detected changes in coastal land cover between 2010 and 2023, while qualitative data from 40 key informants including local residents, tourism operators, and environmental officials were analyzed thematically to understand community perceptions and management responses. Quantitative environmental indicators, such as water quality and coral coverage, were also integrated to assess ecological decline. Results. The findings reveal a significant correlation between the intensity of tourism infrastructure development and the deterioration of coastal ecosystems. Coral coverage declined by 38%, while mangrove areas decreased by 22% within the study period. Stakeholder interviews indicate that weak environmental regulation and poor waste management practices accelerate this degradation. Conclusion. The study concludes that sustainable tourism in southern Bali requires stronger spatial planning, community-based coastal management, and stricter enforcement of environmental standards to balance economic benefits with ecosystem preservation.